2016
DOI: 10.1097/igc.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Radiation Dose in Bone Marrow and Hematological Toxicity in Patients With Cervical Cancer: A Comparison of 3DCRT, IMRT, and RapidARC

Abstract: This study suggests that IMRT results in milder hematological toxicity than either 3DCRT or RapidARC. Dosimetric parameters were associated with the incidence of HT in cervical cancer patients who received concurrent chemoradiotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…This is in particular the case when radiation therapy is delivered to pelvis such as for cervical cancer, rectal cancer and prostate cancer, during which a large proportion of bone marrow is affected (154). Neutrophils are the major innate immune cells that are decreased by radiation therapy.…”
Section: The Tumor Microenvironment Irradiation Dictates Antitumor Inmentioning
confidence: 99%
“…This is in particular the case when radiation therapy is delivered to pelvis such as for cervical cancer, rectal cancer and prostate cancer, during which a large proportion of bone marrow is affected (154). Neutrophils are the major innate immune cells that are decreased by radiation therapy.…”
Section: The Tumor Microenvironment Irradiation Dictates Antitumor Inmentioning
confidence: 99%
“…Approximately half (40-50%) of bone marrow is localized in pelvic region [47,48]. Majority of available clinical data describes the application of intensity modulated radiation therapy (IMRT) for BMS-RT for prostate, cervical, rectum, anal cancers [47,[49][50][51][52][53][54][55][56][57][58]. In macroscopic cervical and rectum cancer dynamic irradiation techniques are still not first-line treatment options due to concerns over internal organ motion [8,9,59].…”
Section: Bone Marrow Sparing Rtmentioning
confidence: 99%
“…In another paper, Wan et al indicated that lumbosacral BM-V40 predicted grade ≤ 2 HT in CRT for rectal cancer [54]. In the study including 100 women, Chang et al noted that IMRT was superior to 3-D RT in medium and high doses (BM-V20, BM-V30, BM-V40) and mean BM dose [55]. Those parameters were most significant for HT in CRT for cervical cancer [55].…”
Section: Total Bone Marrow Sparing Rt In Treatment Areamentioning
confidence: 99%
See 2 more Smart Citations